Parasites and raven mothers: A German-Japanese comparison on (lone) motherhood - Anna Klabunde; Evelyn Korn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
Having a child out of wedlock used to be associated with shame and scorn. This is mostly not the case any more in the western world. Therefore, freed from social sanctions, single motherhood has become an additional family-choice alternative for women, along with marriage and childlessness. Yet, the institutions that influence women's decisions differ across countries. We compare the institutional frame, in particular labor-market characteristics and family law, in Germany and Japan and, in addition, the interaction between culture and institutions. Both countries had a very traditional (one-earner) family system until the second half of the 20th century. Now we can observe that social changes that happened in Germany decades ago are happening only now in Japan. We analyze if and how the consequences in terms of family structures and fertility rates that resulted in Germany can be transfered to Japan.
Keywords: 330; Alleinerziehende; Weibliche Arbeitskräfte; Sozialstaat; Familienrecht; Sozialer Wandel; Vergleich; Deutschland; Japan